FROM THE “PARIS OF THE EAST” TO MODERN PHNOM PENH: COLONIAL LEGACIES IN CAMBODIAN URBAN PLANNING - Ke, Jin; Solihat, Ade (International Review of Humanities Studies, 2026)
Phnom Penh was once known as the “Paris of the East,” serving as a major urban center in Indochina during the French colonial period. Colonial authorities shaped the city through functional zoning, planned street networks, and European-style architecture, all of which reflected hierarchies of power embedded in urban space. Despite the extensive destruction caused by the Khmer Rouge regime and subsequent postwar reconstruction, traces of colonial urban planning and architectural heritage remain clearly visible in the contemporary development of Phnom Penh. This study adopts a literature-based approach combined with historical analysis, spatial analysis, and architectural case studies to examine how colonial legacies have been preserved, transformed, or disrupted in the process of modern urban development. The findings indicate that key road axes and several colonial-era buildings have been retained or adaptively reused, particularly for tourism and commercial purposes. At the same time, market-oriented modernization has contributed to displacement, land-use conversion, and the widening of social inequalities within the city. As a result, the image of Phnom Penh as the “Paris of the East” has gradually faded, while elements of colonial heritage are being reappropriated as cultural assets, instruments of city branding, and symbols of new social status. This study argues that colonial legacies should be reconsidered not merely as remnants of the past, but as active components in an ongoing dialogue shaping a more inclusive urban identity for the future.